Biochemical identification of the catalytic residues of a glycoside hydrolase family 120 β‐xylosidase, involved in xylooligosaccharide metabolisation by gut bacteria. Issue 20 (20th August 2015) - Cecchini, Davide A.; Fauré, Régis; Laville, Elisabeth; Potocki-Veronese, Gabrielle
Abstract : The β‐xylosidase B from Bifidobacterium adolescentis ATCC15703 belongs to the newly characterized family 120 of glycoside hydrolases. In order to investigate its catalytic mechanism, an extensive kinetic study of the wild‐type enzyme and mutants targeting the three highly conserved residues Asp 393, Glu 416 and Glu 364 was performed. NMR analysis of the xyloside hydrolysis products, the change of the reaction rate‐limiting step for the Glu 416 mutants, the pH dependency of E416A activity and its chemical rescue allowed to demonstrate that this GH120 enzyme uses a retaining mechanism of glycoside hydrolysis, Glu 416 playing the role of acid/base catalyst and Asp 393 that of nucleophile. Abstract : The GH120 Ba XylB from Bifidobacterium adolescentis is a retaining β‐xylosidase. Asp 393 and Glu 416 act as nucleophile and acid/base catalyst respectively. Glu 364 is involved in substrate binding.